Comparative water relations of four Mediterranean oak species - Acherar, M.; Rambal, S. (Plant Ecology, 1992)
The water relations and responses of two evergreen (Quercus ilex L. and Q. suber L.) and two decidu- ous (S. afares Pomel. and Q. faginea Will.) Quercus species were studied under experimental conditions. Two-year old seedlings grown in 30 1. pots were subjected to a drying period during which stomatal conductance, pre-dawn potential and minimum foliar potential were measured. The results shows that, for all species, the daily course of stomatal conductance agrees with the patterns proposed by Hinckley et al. (1978 & 1983). Concurrent with the species responses to short-term variation in water availability, it was found that pre-dawn leaf water potential controlled the maximum daily leaf conductance. There was a strong correlation between pre-dawn leaf potential and maximum daily conductance as described by the reciprocal function g ........ = ( -0.47 + 2.61.~bp) 1 for the evergreen oaks and g ......... (-1.94+7.39.~bp) 1 for the deciduous species. These differences between the two groups may partialy explain their geograhic distributions, and suggest general questions concerning the mechanisms which optimize water-use efficiency in Mediterranean oak species.
Keywords: mediterranean species; Quercus; Stomatal conductance; water-potential; water-stress